2006
DOI: 10.1139/g05-097
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a set of disease resistance-gene analogs (RGAs) from wild rice,Zizania latifoliaGriseb. I. Introgression, copy number lability, sequence change, and DNA methylation alteration in several rice–Zizaniaintrogression lines

Abstract: Eight resistance-gene analogs (RGAs) were isolated from wild rice, Zizania latifolia Griseb., by degenerate primers designed according to conserved motifs at or around the nucleotide-binding site (NBS) of known NBS-containing plant resistance genes. The 8 RGAs were classified into 6 distinct groups based on their deduced amino acid sequence similarity of 60% or greater. Gel-blot hybridization of each of the RGAs to 4 rice - Z. latifolia intro gression lines indicated an array of changes at either introgressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Pair-wise sequence comparison of selected loci showed that the variation represented either base substitutions or small insertion/deletions, On the positive side, the same authors report the generation of new diversity with some of the introgression lines showing increased biomass, tolerance to low temperature and plant submergence, and immunity or high levels of resistances to several major rice diseases, It is evident that alien introgression can be highly mutagenic to a recipient plant genome. More recently, Chen et al, (2006) isolated eight resistance-gene analogs from Z. latifolia by using introgression lines and subsequently classified them into six distinct groups. Another method for creating interspecies transgenic hybrids was developed by Zhao et al (1998), who used a "spike-stalk injection" method to transfer exogenous genomic DNA from wild rice, maize, sorghum, Echinochloa crusgalli, and Panicum maximum into the uppermost stem internode at the position just under the panicle base of recipient rice plants at flowering.…”
Section: Developing Transgenics With Large-scale Transfer Of Exogementioning
confidence: 99%
“…Pair-wise sequence comparison of selected loci showed that the variation represented either base substitutions or small insertion/deletions, On the positive side, the same authors report the generation of new diversity with some of the introgression lines showing increased biomass, tolerance to low temperature and plant submergence, and immunity or high levels of resistances to several major rice diseases, It is evident that alien introgression can be highly mutagenic to a recipient plant genome. More recently, Chen et al, (2006) isolated eight resistance-gene analogs from Z. latifolia by using introgression lines and subsequently classified them into six distinct groups. Another method for creating interspecies transgenic hybrids was developed by Zhao et al (1998), who used a "spike-stalk injection" method to transfer exogenous genomic DNA from wild rice, maize, sorghum, Echinochloa crusgalli, and Panicum maximum into the uppermost stem internode at the position just under the panicle base of recipient rice plants at flowering.…”
Section: Developing Transgenics With Large-scale Transfer Of Exogementioning
confidence: 99%
“…Its seeds or young shoots are popular foods or vegetables in China (Guo et al, 2007). Moreover, some eminent traits in Z. latifolia are used for rice breeding owing to its close relationship to rice (Oryza sativa L.) (Chen Y. et al, 2006). And the release of genome sequences of Z. latifolia would greatly accelerate the progress of molecular breeding related to the species (Guo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This epigenetic process can greatly influence levels of gene expression. Recent studies in rice highlighted extensive changes in DNA methylation patterns (as well as gene copy number and sequence) following the introduction, through conventional breeding, of a chromosomal fragment from a related wild species Long et al 2006;Chen et al 2006). These naturally occurring transformations and their induction through stresses and conventional breeding have impacted and will clearly continue to impact the genetic diversity of plants including domesticated crops and, potentially, the composition of foodstuffs derived from such plants.…”
Section: Introductionmentioning
confidence: 99%